Status of wide crosses in cassava and yam - Asiedu, Robert; Bai, K.V.; Terauchi, R.; Dixon, Alfred G.O.; Hahn, S.K. (1992)
Wild relatives of cassava (Manihot spp.) and yam (Dioscorea spp.) have many attributes of importance to the genetic improvement of the cultivated species. Some crosses between cassava and its wild relatives have led to poly ploids (crosses to M. />laziovii and M. epruinosa) and resistance to two major diseases, cassava mosaic virus and cassava bacterial blight (crosses to M. glaziovii). No barriers to interspecific hybridization have been found in the genus Manihot, but hybridization between Dioscorea species is severely hampered by poor and erratic flowering. Much remains to be done in genome analysis in both genera.